Improved dung beetle optimization algorithm and finite element analysis for spindle optimization - Haohao, Ma; As’arry, Azizan; Xuping, Wu; Shah Ismail, Mohd Idris; Ramli, Hafiz Rashidi; Saad, Mohd Sazli; Delgoshaei, Aidin (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This research introduces an integrated optimization methodology for spindle design, combining the improved dung beetle optimization (IDBO) algorithm with finite element analysis (FEA). The IDBO algorithm, enhanced in population initialization and convergence factors, minimizes total deformation and mass, addressing a multi-objective optimization model. The obtained optimal parameters guide the construction of a finite element model, considering additional factors like stiffness and maximum stress. The ensuing FEA produces a foundation for constructing a response surface, further optimized to refine the initial design. Through the combination of the IDBO algorithm and FEA method, the mass of the spindle is reduced from 46.582 kg obtained by the IDBO algorithm solution to 28.479 kg, a total reduction of 38.86%, while meeting design requirements such as maximum total deformation. Modal analysis up to the sixth order validates the design correctness reveals dynamic spindle behavior and guarantees the design requirements. The study demonstrates the reliability and effectiveness of the proposed IDBO algorithm in conjunction with FEA, providing a versatile framework for engineering optimization.